New records of Psomophis obtusus (Cope, 1863) (Serpentes: Dipsadidae) in Argentina and Uruguay - Di Pietro, Diego Omar (2010)
Herein we report the southernmost locality of the genus Psomophis and a new department record of Psomophis obtusus in Uruguay.We analyzed 23 specimens of P. obtusus deposited at the Herpetological Collections of the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia” (MACN), Centro Nacional de Investigaciones Iológicas (CENAI, housed at MACN), and Museo de La Plata (MLP)